Cardiovascular risk factors associated with the mortality of elderly with COVID-19 - Naifi Hierrezuelo Rojas; Luis Enrique Durruty Medina; Alfredo Hernández Magdariaga; Estrella García Gonzales; Tamara Catellano Hardy (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The COVID-19 has affected in a disproportionate way the elderly who have a more unfavorable clinical course.  Objective: To analyze the cardiovascular risk factors associated with the mortality of elderly with COVID-19.  Methods: An analytic, case-control type study, of 25 elderly belonging to the Ramón López Peña Teaching Polyclinic was carried out in Santiago de Cuba, they died due to COVID 19 between January, 2020 and the same month in 2022 (cases) and  50 that didn't die (controls). The ratio of crossed products, confidence interval and attributable risk in exposed percentage were determined.  Results: The age was the risk marker of more association and hypertension was the associated disease of more relevance, for a ratio of crossed products 6.0 and 10.1, respectively.  Conclusions: The findings demonstrated that the patients of advanced age, hypertense, smokers, obese and with cognitive deterioration should be identified, as well as to use a preventive approach that allows the early diagnosis and treatment, to avoid this way fatal outcomes due to COVID-19.